CBD Alleviates Liver Injuries in Alcoholics With High-Fat High-Cholesterol Diet Through Regulating NLRP3 Inflammasome–Pyroptosis Pathway - Jiang, Xuye; Gu, Yingying; Huang, Yuanling; Zhou, Yujia; Pang, Nengzhi; Luo, Jing; Tang, Zhaoyang; Zhang, Zhenfeng; Yang, Lili (Frontiers in Pharmacology, 2021)
Alcohol abuse and high fat diet induced liver diseases have been the most prevalent chronic liver diseases and the leading reasons for liver transplantation around the world. Cannabidiol (CBD) is a botanical component extracted from marijuana plants without psychoactive impact. In our previous reports, CBD can prevent fatty liver induced by Lieber DeCarlie ethanol diet or non-alcoholic fatty liver disease (NAFLD) induced by high fat high cholesterol diet. The current study is a further study on whether CBD can alleviate liver injuries induced by ethanol plus high fat high cholesterol diet (EHFD), which is a model simulating heavy alcohol drinkers in a western diet. A mice liver injury model induced by EHFD for 8 weeks was applied to explore the protective properties of CBD and the underlying mechanisms. We found that CBD prevented liver steatosis as well as oxidative stress induced by EHFD. CBD treatment inhibited macrophage recruitment, and suppressed activation of NFκB-NLRP3-pyroptosis pathway in mouse livers. The hepatoprotective property of CBD in the current model might be a result of inhibition of inflammation via alleviating activation of hepatic NFκB-NLRP3 inflammasome-pyroptosis pathway by CBD.